The Dynamic Stability Problem of Composite Annular Plates with Auxetic Properties - PAWLUS, Dorota (Engineering Transactions, 2023)
This paper presents the effect of the auxeticity on the behaviour of a plate subjected to the loss of stability. The plate structure is composed of three layers built of auxetic or conventional facings and a conventional core. The plate is loaded mechanically in the plane of facings with forces increasing in time. The main technique of the problem solution is based on the orthogonalisation and finite differences methods. Selected examples of plates were calculated with the use of the finite difference method. The obtained results allow observing the similarities and differences between plate models, whose structures are built of conventional layers or mixed layers: auxetic-foam-auxetic. Investigations complement the knowledge of the responses of the composite structures with auxetic properties. They show the possibility of using special plate structures whose materials are characterised by the negative value of Poisson’s ratio.